2022
DOI: 10.3762/bjoc.18.6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of ethyl 2-(oxazolin-2-yl)alkanoates via ethoxycarbonylketene-induced electrophilic ring expansion of aziridines

Abstract: Alkyl 2-diazo-3-oxoalkanoates generate alkoxycarbonylketenes, which undergo an electrophilic ring expansion with aziridines to afford alkyl 2-(oxazolin-2-yl)alkanoates in good to excellent yields under microwave heating. The method is a convenient and clean reaction without any activators and catalysts and can be also applied in the synthesis of 2-(oxazolin-2-yl)alkanamides and 1-(oxazolin-2-yl)alkylphosphonates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Carrying out Wolff rearrangement under microwave irradiation has previously been shown to have several advantages. 26,27 For example, in our case, using microwaveassisted decomposition of diazo tetramic acids, we observed some acceleration of the reaction compared to the reaction with conventional heating, less tar formation, and better reproducibility. Therefore, we switched to using microwave activation for all subsequent experiments.…”
mentioning
confidence: 58%
“…Carrying out Wolff rearrangement under microwave irradiation has previously been shown to have several advantages. 26,27 For example, in our case, using microwaveassisted decomposition of diazo tetramic acids, we observed some acceleration of the reaction compared to the reaction with conventional heating, less tar formation, and better reproducibility. Therefore, we switched to using microwave activation for all subsequent experiments.…”
mentioning
confidence: 58%
“…Alkoxycarbonylketenes ( 196 ), generated from alkyl 2-diazo-3-oxoalkanoates ( 194 ), were employed as substrates for the electrophilic ring expansion of aziridines ( 195 ) in order to obtain alkyl 2-(oxazolin-2-yl)alkanoates ( 197 ) under microwave irradiation. 59 The corresponding final compounds ( 197 ) were obtained in good yields; in all cases, the formation of 1 : 1 mixtures of diastereomeric products was observed (Scheme 36).…”
Section: Reactions Of Aziridinesmentioning
confidence: 95%
“…19 Mixed approaches of photo-and metal-catalysis have also been reported for the synthesis of aziridines. 20 Koenigs et al described the preparation of trifluoromethylated aziridines (62) starting from fluorinated olefins (58) and iodinanes (59), which undergo oxidative quenching in the presence of a Ru (bpy) 3 Cl 2 catalyst (60), releasing a nitrene radical anion (61) (Scheme 11). Computational studies confirmed that the nitrene radical (61) serves as a reactive intermediate in direct aziridination reactions.…”
Section: Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…The nucleophilic ring expansion of saturated three-membered heterocycles has been well investigated [52]. Recently, the electrophilic ring expansion of saturated three-membered heterocycles was also realized [18,53,54]. In contrast with the nucleophilic ring expansion of saturated three-membered heterocycles [52], their electrophilic ring expansion is a new avenue to construct new heterocyclic compounds [18,53,54].…”
Section: Asymmetric Synthesis Of β-Lactams and Deoxygenation Of Oxira...mentioning
confidence: 99%
“…Recently, the electrophilic ring expansion of saturated three-membered heterocycles was also realized [18,53,54]. In contrast with the nucleophilic ring expansion of saturated three-membered heterocycles [52], their electrophilic ring expansion is a new avenue to construct new heterocyclic compounds [18,53,54]. The electrophilic ring expansion of polycyclic arylthiiranes 64 and ketenes K generated from aryloxyacetyl chlorides 63 in the presence of triethylamine is a new strategy for the synthesis of areno[d]ε-thiolactones 66 directly without catalysts or additives.…”
Section: Asymmetric Synthesis Of β-Lactams and Deoxygenation Of Oxira...mentioning
confidence: 99%